2012
DOI: 10.1371/journal.pone.0052326
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle-Mediated Transfer of the Viral Receptors CAR and CD46, and the CFTR Channel in a CHO Cell Model Confers New Functions to Target Cells

Abstract: Cell microparticles (MPs) released in the extracellular milieu can embark plasma membrane and intracellular components which are specific of their cellular origin, and transfer them to target cells. The MP-mediated, cell-to-cell transfer of three human membrane glycoproteins of different degrees of complexity was investigated in the present study, using a CHO cell model system. We first tested the delivery of CAR and CD46, two monospanins which act as adenovirus receptors, to target CHO cells. CHO cells lack C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The diameter of EVs ranges from 30 nm to 1 µm depending on the shedding process, cell type, and cellular compartments from which they are issued (Burger et al, 2004;György et al, 2011György et al, , 2012van der Pol et al, 2012). Recent reviews have highlighted the huge medical potential of EVs as clinically relevant biomarkers and as conveyors of bioactive therapeutic agents (Mause & Weber, 2010;György et al, 2011;Goldberg & Klein, 2012;Gonzalez et al, 2012;van der Pol et al, 2012;). Indeed, EVs have metabolic and signaling importance owing to their pivotal role in information transfer between cells and waste management.…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of EVs ranges from 30 nm to 1 µm depending on the shedding process, cell type, and cellular compartments from which they are issued (Burger et al, 2004;György et al, 2011György et al, , 2012van der Pol et al, 2012). Recent reviews have highlighted the huge medical potential of EVs as clinically relevant biomarkers and as conveyors of bioactive therapeutic agents (Mause & Weber, 2010;György et al, 2011;Goldberg & Klein, 2012;Gonzalez et al, 2012;van der Pol et al, 2012;). Indeed, EVs have metabolic and signaling importance owing to their pivotal role in information transfer between cells and waste management.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that microparticle-mediated transfer of viral receptors confers new functions to the target cells [37] . The current study confirmed the transferred expression of syndecan-1 to the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…anemia and media calcifications in addition to the disturbed bone turnover, thus combining the most important CKD complications. 9 The effects of RAP-011 on bone occurred without affecting serum PTH levels, which, although unexpected, is an interesting observation from a mechanistic point of view because it points toward factors others than PTH that directly modulate osteoclastogenesis and possibly osteoblastogenesis. Here, again, it would be worthwhile to investigate whether the following occurs in animals with severe hyperparathyroidism/osteitis fibrosa, (i) these factors also would be able to overrule the PTH-induced effects on bone cells, (ii) other ligands (e.g., TGF-b)/receptors (e.g., TGF-b receptor 1) might be active, and (iii) inhibitors of the Wnt-b-catenin signaling pathway other than Dkk1 (e.g., sclerostin) are involved in downstream activin signaling.…”
mentioning
confidence: 87%
“…This finding is in line with previous reports, demonstrating that transmembrane proteins like CCR5, CD46, and CFTR channels are transferred by microvesicles and confer new functions to target cells. 8,9 However, it is still unclear whether the microvesicles directly fuse with the plasma membrane of the acceptor cell or whether microvesicles are taken up by endocytosis and fuse with intracellular compartments with subsequent recycling of membrane components to the plasma membrane. A recent study suggests that the latter may be the case.…”
Section: B1-receptormentioning
confidence: 99%